2004
DOI: 10.1007/s10157-004-0291-1
|View full text |Cite
|
Sign up to set email alerts
|

Bisalbuminemia in chronic kidney disease

Abstract: Hereditary and acquired bisalbuminemia, in which the serum contains an albumin variant differing from albumin A by single amino-acid substitutions, have been reported in different races or ethnic groups and in association with various pathologic states. The importance of this rare condition in the pathophysiology of established diseases is uncertain. We evaluated a 68-year-old woman with chronic kidney disease who presented with worsened serum creatinine concentration despite lack of dietary or medical changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…Taking into account the electrophoretic mobility and high abundance of both protein peaks, we suggest that these individuals have bisalbuminemia, similar to what occurs in subspecies of Salamandra 15 . Bisalbuminemia has been well described in humans and can be either hereditary or acquired 16 . In iguanas, bisalbuminemia probably has a genetic origin, based on the symmetric shape of the double peak and its lack of association with a specific disease or pharmacological treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the electrophoretic mobility and high abundance of both protein peaks, we suggest that these individuals have bisalbuminemia, similar to what occurs in subspecies of Salamandra 15 . Bisalbuminemia has been well described in humans and can be either hereditary or acquired 16 . In iguanas, bisalbuminemia probably has a genetic origin, based on the symmetric shape of the double peak and its lack of association with a specific disease or pharmacological treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this abnormality, albumin may either have increased (fast type variants), or decreased electrophoretic mobility (slow type variants; Kobayashi et al 1995). In humans, bisalbuminaemia has been described in some pathological conditions, including chronic renal diseases, nephrotic syndrome, diabetes mellitus, pancreatic doi: 10.17221/19/2016-VETMED disease or Alzheimer's disease (Ejaz et al 2004;Shetty et al 2007). In animals, bisalbuminaemia was found in female bottlenose dolphin (Turiops truncatus), but it was not associated with disease (Medway 1979).…”
Section: Albuminmentioning
confidence: 99%
“…Bisalbuminemia is an inherited or acquired condition with a worldwide cumulative population frequency of [3]. About 77 mutations of albumin gene are known so far and 65 of them were result of bisalbuminemia [4].…”
Section: Discussionmentioning
confidence: 99%
“…Although possibility that some physiologic or pharmacologic substances may not bind to abnormal albumin variant as well as they bind to normal albumin variants as well as they bind to normal albumin should not be discounted [3] In Indian context, Dash et al, found 2 out of 1000 cases screened for bisalbuminemia in Punjabi population [7] Jamal et al, reported two cases of bisalbuminemia in 3000 consecutive electrophoresis in their lab and Simundic A, et al, found about 8 cases of bisalbuminemia in 6500 capillary electrophoresis [4,8].…”
Section: Discussionmentioning
confidence: 99%